ANALYSIS OF THE EFFECTS OF THE COVID-19 PANDEMIC ON MUTUAL FUND PERFORMANCE (USING THE SHARPE METHOD) - Yosua Yerdian (SEAN Institute, 2023)
The phenomenon of the COVID-19 pandemic that occurred in 2020 in Indonesia has more or less influenced the investment climate in Indonesia, especially in mutual fund investment. It is known that mutual funds are an investment that is on the rise, so this study aims to provide information regarding the impact of the COVID-19 pandemic on the performance of 4 types of mutual funds, namely equity funds, money market, fixed income, and mixed mutual funds. The performance analysis method uses risk adjusted return in this case the Sharpe Ratio. Then the best performance of mutual funds was found that money market mutual funds had the best performance with a Sharpe ratio value of 0.1325, followed by equity funds of 0.0670, mixed -0.000066, and the lowest performance of fixed income mutual funds with a Sharpe ratio value of -0.000075. The performance of stock and money market mutual funds also showed better performance than risk free performance, while the other two mutual funds were negative. However, even though the investment performance of mutual funds increased, the performance of all mutual funds was still lower than the performance of the JCI, which had a Sharpe ratio of 0.1675, so that in the final period of the research, stock investment was more profitable than investment in mutual funds. It can be concluded that for mutual funds other than stocks, it shows that COVID-19 did not significantly affect fluctuations in mutual fund returns before and after the announcement of COVID-19 in Indonesia.